2006
DOI: 10.1111/j.1464-410x.2006.06179.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tumour location on the histological subtype of renal cortical tumours

Abstract: extend into the collecting system, hilum, or renal sinus. A lesion that did not meet these criteria was defined as a central lesion. Logistic regression analysis was used to determine if either type of lesion had a greater representation of any histological subtype. A two-tailed P ≤ 0.05 was considered to indicate significance. RESULTSOf the 485 RCTs, 171 (35%) were exophytic and 314 (65%) were central, while 308 (64%) were clear cell and 177 (36%) were non-clear cell tumour histology. Of the exophytic lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Similarly, multiple studies have demonstrated tumor location is correlated with biologic potentiation, with exophytic tumors exhibiting less malignant lesions and less clear cell histology. [22, 23] Together these studies along with the present study suggest that increasing anatomic complexity is associated with more aggressive biologic potential.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, multiple studies have demonstrated tumor location is correlated with biologic potentiation, with exophytic tumors exhibiting less malignant lesions and less clear cell histology. [22, 23] Together these studies along with the present study suggest that increasing anatomic complexity is associated with more aggressive biologic potential.…”
Section: Discussionsupporting
confidence: 74%
“…Those treated with radical nephrectomy were more likely to have larger tumors, clear cell histology, and perinephric or renal sinus fat invasion, all features reported to increase the risk of cancer-specific death. 17-19 Furthermore, we also suggest that patients treated with partial nephrectomy in the current study were more likely to have exophytic tumors, which may be biologically less aggressive than more central or hilar renal masses, 20 perhaps due to the close proximity of the renal sinus with its associated rich network of veins and lymphatics. 21 Additionally, surgeon selection bias may have influenced the results in that more aggressive appearing tumors may have been selected for radical nephrectomy.…”
Section: Discussionmentioning
confidence: 61%
“…For example, Schachter et al reported that exophytic lesions were significantly more likely to be non–clear cell tumors when compared with central lesions ( p = 0.003), although no standardized definition of “exophytic” was provided [10]. In 123 patients undergoing laparoscopic partial nephrectomy, Venkatesh et al reported that only 55% of “highly exophytic” tumors were malignant, and of those, nearly all (96%) were low grade [11].…”
Section: Discussionmentioning
confidence: 99%